Predictors of confidence in research: a cross-sectional survey of pharmacists in the north of England. - Wilson, Franki; Pieniazek, Rebecca; Hodgins, Mike; Jamieson, Hazel; Brown, Jane; Forsyth, Paul (International Journal of Pharmacy Practice, 2024)
Objective: Pharmacist-led research is key to optimizing medicines use and improving pharmacy services, yet it is not yet widely embedded into careers. This study aims to identify predictors of confidence in meeting the research learning outcomes in the Royal Pharmaceutical Society (RPS) Post-Registration Foundation and Core Advanced curricula, to provide targeted recommendations for building research capability and capacity within the profession. Methods: The study was a cross-sectional electronic survey, distributed to eligible pharmacists in March 2023 (n = 253). The survey gathered demographic information, research experience, and self-reported confidence in meeting the research learning outcomes in the RPS Post-Registration Foundation and Core Advanced curricula. Pre-determined independent variables were analysed using two binomial logistic regression models (one per curriculum) to identify predictors of the dichotomous variable: confidence with meeting all research learning outcomes in that curriculum. Key findings: Participants were more likely to self-report as confident (versus not confident) with meeting all research learning outcomes in a curriculum if they had recent experience (within the previous 12 months) of research or research-related activities, held a postgraduate research qualification, had undertaken research training outside of a postgraduate qualification, discussed research in their appraisal, or worked in the hospital sector. Conversely, male gender, years practicing, and protected time for research did not predict confidence. Conclusion: A targeted approach, including improving access to research methods training, experience-based learning, mentorship, and linking research projects to key organizational objectives, could be the key to developing research capability and capacity across all sectors and career stages.